Implementation Of Statement Of Financial Accounting Standards (PSAK) 112 In The Financial Statements Of The Assyifa Waqf Agency In Subang District - Ramadhani Irma Tripalupi; Iwan Setiawan; Gita Zakiah; Nurhasanah, Mia; Qheista Noor Fiddienillah (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2024)
This study investigates the implementation of SFAS 112 in the financial statements of the Assyifa Waqf agency in Subang Regency. Using qualitative research methods, the study aims to accurately describe the agency's financial statements using primary and secondary data. The data collection techniques include literature study, documentation, interviews, and observation. The recognition of waqf assets based on nominal and fair values, and the presentation of financial statements, including statements of financial position, activities, cash flows, and changes in assets under management, are key areas of focus. It is noted that the full implementation of SFAS112 in the Assyifa Waqf Board, particularly in terms of recognition, measurement, presentation, and disclosure of financial statements, has not been achieved. The findings of this study could potentially have a significant impact on the field of Islamic economics and waqf practices, providing valuable insights for future research and practice.